Characterisation on grade of waste concrete particle reinforced aluminium AA7075 based composite - Zaman, Khaizuran Irfan; Abdul Latif, Dr.Noradila (Research Progress in Mechanical and Manufacturing Engineering, 2023)
A composite is a material made up of elements generated by physically merging pre-existing monolithic compounds to produce a new material having properties separate from the original composition. In the engineering area, AMC is commonly employed in the product. This is owing to its performance and unique qualities as a result of the reinforcement's added features. The investigation materials for this study were aluminium alloy AA7075. The solid-state technology is used in this work to explore the influence of waste concrete as a reinforcement material in metal matrix composites because it has significantly lower operation costs and energies than traditional recycling by casting. The mechanical and physical qualities of waste concrete materials for Grades 40 and 30 with zinc stearate as a binder were examined. On each reinforcement composition, recycled aluminium chi AA7075 was reinforced with 2.5 %, 5 %, 7.5 %, 10 %, and 12.5 % waste concrete materials, as well as 1 % zinc stearate. The current study looked at the density, apparent porosity, water absorption, micro-hardness, compression, and microstructure of aluminium matrix composites. The addition of 1 wt. % zinc stearate to the decrement of density for metal matrix composites down to 7.5 wt %. waste concrete materials then rose with the increment of waste concrete materials percentage. Chip AA7075 hardness increased as the mass fraction of waste concrete materials increased, from 46.71 Hv to 49.15 Hv for both grades and zinc stearate, and subsequently decreased from 49.15 Hv to 33.32 Hv for Grade 40. In other hand for Grade 30 mass fraction of concrete waste has increase from 28.23 Hv to 55.33 Hv then decrease to 45 Hv. The Young’s Modulus of chip AA7075 for reinforcement with waste concrete Grade 40 and constant zinc stearate composition has also improved from 11.31 N/ to 11.656 N/   but then it’s decreasing as the amount of waste concrete in the composition increasing and it’s also happen to AA7075 for reinforcement with waste concrete materials Grade 30 and constant addition of zinc stearate composition where the Young’s Modulus increasing from 11.31 N/ to 13.24 N/ and decreasing when the composition of waste concrete increase.